Menghidupkan Kembali Bank Sampah Pasca Pandemi Covid 19 RT 06 RW 09 Landungsari Malang - Putri, Ronasari Mahaji; Devi, Hilda Mazarina (Jurnal Abdimas Kesehatan (JAK), 2024)
PKK RT 06 RW 09 is a forum for gathering mothers in the village of Tirtosari RT 06 RW9 Landungsari Malang, with 45 members. The location of the Tirtosari village is close to the Final Garbage Shelter (TPAS), so it was found that many mosquitoes and sometimes the smell of garbage enters residential areas. Garbage bank activities at that location have been inactive for a long time, and this community service was carried out as an effort to revive waste bank activities in Tirtosari Village. Lack of knowledge from PKK mothers, the perception that the house is dirty because of hoarding trash and reluctance to collect and sort waste are the problems faced by Servants. Community service activities which include counseling on waste management by the Village Garbage Bank Team and waste bank activities (collection, sorting, depositing, weighing and recording waste) are carried out smoothly. Even though the visit target was not met (only 22 of the 44 women who were planned to attend), this activity was able to increase waste bank visits (from 7 mothers to 20 mothers) who participated in waste bank activities. It is hoped that this activity can continue and provide benefits for Kampung Tirtosari